Physical properties of concrete containing coconut shell as coarse aggregate - Nor Azlinda Binti Abdullah (School of Environmental Engineering, University Malaysia Perlis, 2014)
The increasing price of development content is a matter of issue. The reason for improve in price is popular requirement of concrete and lack of raw material. Hence the concrete technologists must search for some cost-effective substitute to the coarse aggregate. Physical properties of concrete with the coconut shell aggregate (CSA) as coarse aggregate replacements were studied.